Теории среднего уровня: место в структуре социологического знания и тенденции развития (Историографический анализ на материале стран СНГ) - Городяненко, В. (Социология: теория, методы, маркетинг, 2001)
The article presents historiography of the middle level theories in the sociological knowledge structure. Taking into account their history and specific characters, the author determined the main development tendencies of the theories, like sociology of labor, economy, entrepreneurship, and discussed some aspects of historiography systematization and classification applied to the sociological middle level theories.